2020
DOI: 10.37268/mjphm/vol.20/no.2/art.250
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Rodents Infected With Leptospira Bacteria in Various Countries and the Leptospirosis Potential in Humans: A Systematic Review

Abstract: Leptospirosis is an infectious disease caused by Leptospira bacteria. It is a global public health concern, especially in tropical and subtropical regions. The aim of this review was to summarize some relevant studies that discuss the presence of rodents and the identification of Leptospira bacteria in rodents. This review also presents findings on the potential reassociation of the presence of rodents with Leptospira bacterial infections to leptospirosis cases in humans. A systematic review methodology used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The concept of exposure varies widely in different parts of the world, with the mean incidence constituting the highest among the environmental factors, according to Daud et al [24]. Tantia et al [25] revealed that rodents are known to be the most prevalent source of leptospirosis in humans. Those infected with Leptospira are linked to a high frequency of leptospiral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of exposure varies widely in different parts of the world, with the mean incidence constituting the highest among the environmental factors, according to Daud et al [24]. Tantia et al [25] revealed that rodents are known to be the most prevalent source of leptospirosis in humans. Those infected with Leptospira are linked to a high frequency of leptospiral transmission.…”
Section: Discussionmentioning
confidence: 99%